Facilitated Lattice Oxygen Depletion in Consolidated TiO2 Nanocrystal Ensembles: A Quantitative Spectroscopic O2 Adsorption Study - Elser, Michael J.; Diwald, Oliver (Journal of Physical Chemistry C, 2012)
On TiO2 nanocrystal powders, pressure-induced consolidation and subsequent annealing generates mesopores inside the pellet and leads to the depletion of specific surface area. This loss corresponds to the introduction of particle–particle interfaces and grain boundaries. In previous work, they were found to be susceptible to facilitated lattice oxygen depletion as compared to free particle surfaces during vacuum annealing. For the first time, we determined the adsorption of molecular oxygen on these consolidated and nonstoichiometric nanocrystal samples. As a function of repeated cycles of vacuum annealing and O2 exposure, the amount of paramagnetic and diamagnetic surface oxygen species was determined using mass spectroscopy in combination with FT-IR, electron paramagnetic resonance (EPR), and UV–vis–NIR diffuse reflectance.
EAM Import::2019-03-14